Establishment of an in vitro 3D model for neuroblastoma enables preclinical investigation of combined tumor‐stroma drug targeting. Issue 8 (5th July 2020) - Kock, Anna; Bergqvist, Filip; Steinmetz, Julia; Elfman, Lotta H. M.; Korotkova, Marina; Johnsen, John Inge; Jakobsson, Per‐Johan; Kogner, Per; Larsson, Karin
Abstract: The majority of anti‐cancer therapies target the proliferating tumor cells, while the tumor stroma, principally unaffected, survives, and provide a niche for surviving tumor cells. Combining tumor cell and stroma‐targeting therapies thus have a potential to improve patient outcome. The neuroblastoma stroma contains cancer‐associated fibroblasts expressing microsomal prostaglandin E synthase‐1 (mPGES‐1). mPGES‐1‐derived prostaglandin E2 (PGE2 ) is known to promote tumor growth through increased proliferation and survival of tumor cells, immune suppression, angiogenesis, and therapy resistance, and we, therefore, hypothesize that mPGES‐1 constitutes an interesting stromal target. Here, we aimed to develop a relevant in vitro model to study combination therapies. Co‐culturing of neuroblastoma and fibroblast cells in 3D tumor spheroids mimic neuroblastoma tumors with regard to the cyclooxygenase/mPGES‐1/PGE2 pathway. Using the spheroid model, we show that the inhibition of fibroblast‐derived mPGES‐1 enhanced the cytotoxic effect of doxorubicin and vincristine and significantly reduced tumor cell viability and spheroid growth. Cyclic treatment with vincristine in combination with an mPGES‐1 inhibitor abrogated cell repopulation. Moreover, inhibition of mPGES‐1 potentiated the cytotoxic effect of vincristine on established neuroblastoma allografts in mice. In conclusion, we established a 3D neuroblastoma model, highlighting the potential of combining stromal targeting of mPGES‐1 with tumor cell targeting drugs like vincristine.